2019
DOI: 10.15593/2224-9826/2019.2.10
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Structure Forming Factors on Low-Cycle Fatigue of a Polymer Composite Material Based on Furfural Acetone Monomer (Fam)

Abstract: Research studies of polymer concretes are frequently carried out under the action of static loads while the material is affected by cyclic loads, most often, low-cycle as a result of its work in the structure. In the case when the level of stresses caused by these loads exceeds a certain limit, irreversible damage accumulation processes begin to occur in the material, which lead to the formation of cracks. In the future, the stress concentration at the edge of the crack contributes to its development. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The best results were shown in the treatment modes at 80 o C for 10 hours and at 100 o C for 8 hours. It can be concluded that heating of polymer concrete intensifies polymerization of the FD binder [17,18,21].…”
Section: Manufacturing Technology For Building Materials and Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…The best results were shown in the treatment modes at 80 o C for 10 hours and at 100 o C for 8 hours. It can be concluded that heating of polymer concrete intensifies polymerization of the FD binder [17,18,21].…”
Section: Manufacturing Technology For Building Materials and Productsmentioning
confidence: 99%
“…The strength of polymer concrete is determined by many factors [16][17][18]. The main ones include: the content of the binder and hardener amounts in polymer concrete, the hardening mode, and the mineral and petrographic characteristics of aggregates.…”
mentioning
confidence: 99%
See 1 more Smart Citation